Keyakinan dan mathematics pedagogical content knowledge calon guru matematika: fokus pada domain bilangan - Farman, Farman; Ekawati, Rooselyna; Masriyah, Masriyah (IKIP Siliwangi, 2023)
The purpose of this study was to identify and describe the beliefs and mathematics pedagogical content knowledge (MPCK) of pre-service mathematics teachers. This research is a type of quantitative research with a descriptive design. This research involved 29 final year mathematics pre-service teacher at a college in Southeast Sulawesi, Indonesia. The instruments used in this study were a confidence questionnaire and the MPCK test based on the TEDS-M indicator. The data analysis technique used in this research is descriptive analysis technique. The results showed that the pre-service teacher's belief in mathematics and teaching mathematics was in the high category. Meanwhile, the MPCK of pre-service teachers is in the less category. This shows that pre-service teachers still have difficulties in planning appropriate activities, appropriate methods, predicting student responses, evaluating student mathematical solutions, identifying student misconceptions and representing mathematical concepts or procedures. Future research may consider expanding the focus on the predictive relationship between belief and MPCK pre-service teachers.